149k views
4 votes
SOLVE THIS: 6(2x+3) =42

1 Answer

2 votes

Answer:

x = 2

Explanation:

First, distribute 6 to all terms within the parenthesis.

6(2x + 3) = 12x + 18

Isolate the variable x. Note the equal sign, what you do to one side, you do to the other. Do the opposite of PEMDAS.

12x + 18 = 42

First, subtract 18 from both sides.

12x + 18 (-18) = 42 (-18)

12x = 24

Isolate the variable x. Divide 12 from both sides.

(12x)/12 = (24)/12

x = 24/12

x = 2

2 is your answer for x.

~

User Vivianne
by
4.9k points